A Cationic Oligomer as an Organic Template for Direct Synthesis of Aluminosilicate ITH Zeolite - Lei, Chi; Dong, Zhuoya; Martínez, Cristina; Martínez‐Triguero, Joaquín; Chen, Wei; Wu, Qinming; Meng, Xiangju; Parvulescu, Andrei‐Nicolae; De Baerdemaeker, Trees; Müller, Ulrich; Zheng, Anmin; Ma, Yanhang; et al. (Angewandte Chemie International Edition, 2020)
There are a large number of zeolites, such as ITH, that cannot be prepared in the aluminosilicate form. Now, the successful synthesis of aluminosilicate ITH zeolite using a simple cationic oligomer as an organic template is presented. Key to the success is that the cationic oligomer has a strong complexation ability with aluminum species combined with a structural directing ability for the ITH structure similar to that of the conventional organic template. The aluminosilicate ITH zeolite has very high crystallinity, nanosheet‐like crystal morphology, large surface area, fully four‐coordinated Al species, and abundant acidic sites. Methanol‐to‐propylene (MTP) tests reveal that the Al‐ITH zeolite shows much higher selectivity for propylene and longer lifetime than commercial ZSM‐5. FCC tests show that Al‐ITH zeolite is a good candidate as a shape‐selective FCC additive for enhancing propylene and butylene selectivity. Oligomers to the aid of ITH: A way to directly synthesize aluminosilicate ITH (Al‐ITH) zeolite using a cationic oligomer as an organic template is presented: The strong complexation ability with aluminum species is a key factor for the successful preparation.